Seroprevalence of Hepatitis-B surface antigen among the patients reporting at tertiary care Hospital from India - Patil, Satish R; Ghorpade, MV; Patil, Supriya Satish; Pawar, SK; Mohite, ST (Bangladesh Journal of Medical Science, 2016)
Background: Hepatitis B is a potentially life-threatening liver infection caused by the hepatitis B virus. It is a global health problem. Objectives: To estimate the Seroprevalence of HBsAg and its age and sex wise distribution in a hospital based population. Materials and Methods: Serum samples collected over a period of 12 months from patients attending OPDs and admitted to various IPDs of Krishna Hospital and Medical Research Center Karad, were included in the study. Seroprevalence of Hepatitis B surface antigen among hospital based general population was determined using a third generation ELISA. Statistical analysis: Percentages, chi square test. Results: A total number of 7373 patients were screened for HBsAg, among them 3238 (43.92%) were males and 4135 (56.08%) were females. The seroprevalence of HBsAg was 166 (2.25%). The seroprevalence of HBsAg was higher in males 85 (2.63%) as compared to females 81 (1.96%). The highest seroprevalence was found to be among 51-60 years age group (5.24%). Bangladesh Journal of Medical Science Vol.15(3) 2016 p.455-459